Epidemiological and clinical variables in pediatric patients hospitalized for urinary tract infection - Isabel María Vallina López; Rolando Rodríguez Puga; Yasnier Dueñas Rodríguez; Yoánderson Pérez Díaz; María Emilia Navarro Huertas; María Francisca Garcés Raventós (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
Foundation: urinary tract infection is one of the most common diseases in children and presents with non-specific symptoms, especially in younger children, in which the most important sign is fever. Objective: to characterize a series of pediatric cases hospitalized due to urinary tract infection. Methods: a descriptive study, of a case series type, was carried out at the Pediatric Hospital of Camagüey, from January to March 2023. The sample was made up of 112 patients, once the selection criteria were applied. The studied variables were: age group and sex, health area, clinical signs and symptoms, risk factors and isolated germs. Data processing was carried out using the statistical package for the social sciences and the results were expressed in absolute values and percentages. Results: the age group of children under one year (31.2%) and the female sex (68.7%) predominated. The Finlay Health Area was the one that contributed the most cases (22.3%), while fever was the predominant symptom (93.8%), as well as abandoning breastfeeding as the main risk factor (25.9%). In 32.1% of the cases the Escherichia coli germ was isolated. Conclusions: urinary tract infection is more frequent in female infants, and fever is confirmed as the main symptom, in addition to the abandonment of breastfeeding being collected as a substantial risk factor.